Tingkat Pengetahuan Masyarakat Mengenai Manfaat Berwudhu Bagi Kesehatan Gigi dan Mulut - Chotimah, Chusnul; Salim , Andi Nur Annisa; Suherman , Patricia Luthfiah (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Five times a day, various parts of the body are washed as part of a personal hygiene ritual known as "wudu." Ablution itself includes two aspects of cleanliness: external cleanliness, which is achieved by cleaning the various parts of the body. It is sunnah to perform ablution before dhikr, before going to bed (especially for menstruating or junub women), before taking a mandatory bath, and at obligatory times. It is ordered to perform ablution tajdid, which is to repeat ablution even though you are still clean. This will only increase the reward and refresh the ablution before prayer. Furthermore, the concept of ablution is usually not associated with the practice of cleaning oneself before prayer or performing other acts of worship Depends on the context of the sentence. Ablution provides several health benefits, such as removing dirt, bacteria, and viruses from the mouth, nose, teeth, and ears, and encouraging the regeneration of mucous membranes. By doing this, the possibility of moderate to severe infections entering through certain areas of the body can be reduced. The benefits of ablution for dental and oral health are to eliminate bad breath, maintain dental health and prevent periodontal disease.